Curricular environmentalization in higher education: the Brazilian interpretation of scenarios under the light of complex thinking - Modesto, Mônica Andrade; Araujo, Maria Inêz Oliveira (Debates em Educação, 2020)
The curricular environmentalization presents itself as a viability for the formation of critical and co-responsible subjects with the (re)construction of a better world. The methodological procedures used in this article were the qualitative approach and the Complex Hermeneutic-Phenomenological Approach (AHFC) and made it possible to understand that, in Brazil, the experiences related to curricular environmentalization point to a scenario in which attempts are made to evidence the environmental education in Higher Education, however, despite the successful attempts, there is still much to be considered. This interpretation is due to the analysis of the state of knowledge of the scientific productions about the theme in question and the possibilities for its implementation are focused in actions based on the environmental dimension of the curriculum, or on thematic and punctual actions.